Twentieth-Century Changes in Catholic Liturgy and the Place of Truth in Religious Culture: A Discussion with Chantal Delsol - Tomasz Dekert (Religions)
This article explores the transformative changes in Catholic liturgy during the twentieth century and their implications for the stability of religious meaning and cultural identity in the West. In critical dialogue with Chantal Delsol’s diagnosis of the decline of Christianitas, this study argues that the reform of ritual following the Second Vatican Council, rather than political entanglements, played a decisive role in weakening the public credibility of Catholic truth claims. Drawing on Roy A. Rappaport’s theory of ritual as a stabilizer of cultural meaning, the author analyzes how this postconciliar liturgical reform altered the semiotic structure of Catholic worship—shifting communication from indexical to symbolic forms and reorienting the liturgy from a vertical–concentric order to a more decentralized horizontal dynamic. The chosen method combines theoretical reflection with liturgical anthropology to assess how changes in the Roman Missal, ritual posture, and spatial arrangement disrupted the transmission of canonical messages. The conclusion suggests that this semiotic transformation undermined the liturgy’s capacity to ritually confirm the truths of faith, contributing to the broader civilizational disintegration observed by Delsol. Ultimately, this article contends that any future revitalization of Catholic culture will depend less on political influence and more on recovering the liturgy’s ritual capacity to sustain belief in transcendent truth.